Comparative ethnobotanical analysis of medicinal plants in the Western Tien Shan Transboundary Region using an integrated approach: A comparison with the Nurata Range - Kosimov, Zokir; Bussmann, Rainer W.; Shomurodov, Kh.F.; Beshko, N.Yu.; Kodirov, U.H.; Azimova, D.E.; Sayfullayeva, S.H.; Turginov, O.T. (Ethnobotany Research and Applications, 2026)
Background: Mountain ecosystems of Central Asia represent key centers of biological and cultural diversity, yet comparative quantitative assessments of medicinal plant use across ecologically contrasting mountain systems remain limited. This study aims to evaluate the ethnobotanical significance of medicinal plants in the Western Tien Shan transboundary region and compare the results with the Nurata Range using an integrated assessment model. Methods: Medicinal plant species were selected based on documented traditional use and confirmed occurrence within each region. A total of 185 species from Western Tien Shan and 110 species from Nurata were evaluated using the Ethnobotanical Value Index (EVI), calculated as the mean of five equally weighted parameters: use diversity, chemical richness, plant part diversity, preparation diversity, and additional functional value. Floristic similarity between regions was assessed using the Jaccard similarity coefficient. Results: Western Tien Shan exhibited higher species richness, while Nurata showed a higher mean EVI value (2.97 vs. 2.32), indicating stronger knowledge concentration. A greater proportion of high-EVI species (≥3.0) was recorded in Nurata, whereas Western Tien Shan displayed a more dispersed distribution across value categories. Jaccard analysis (J = 0.45) revealed moderate similarity, with 91 shared species and substantial regional differentiation. Conclusion: The findings demonstrate that species richness and ethnobotanical use intensity represent distinct structural dimensions of traditional knowledge systems. The integrated EVI framework provides a quantitative basis for prioritizing medicinal plant species and supports conservation-oriented management strategies in transboundary mountain ecosystems of Central Asia. Keywords: Ethnobotany; Medicinal plants; Western Tien Shan; Nurata Range; Ethnobotanical Value Index (EVI); Transboundary mountain ecosystems; Central Asia; Floristic similarity; Traditional knowledge systems.